WANPRESTASI DALAM PELAKSANAAN KONTRAK BISNIS ANTARA BIRO PERJALANAN WISATA “GOH” DENGAN JAYAKARTA HOTEL DI LEGIAN - Sriartini, Ni Kadek; Purwanti, Ni Putu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 09, September 2013)
This article with title the default in the conduct of business between the travel agency “Goh” with Jayakarta hotel in Legian. Business contract that made between the trevel agency “Goh” with Jayakarta Hotel is a written agreement. Where in the agreement that has been determined rents rooms, time of payment, time of arrival, and time of departure. From that agreement, the travel agency “Goh” doesn’t perform their obligations to pay rents rooms on time, so the Jayakarta Hotel suffered losses. So this problem triggeres the writer to raise this issue by the efforts that can be taken by the parties to resolve legal issies. And the purpose of this paper is to determine the settlement of legal issue arising from defaults in the execution of the contract between the travel agency business with Jayakarta Hotel in Legian. This research applied empirical yuridical research. The settlement of the legal issues is solved by negotiating between goh and hotel to get the best solution.
Keywords: Settlemen, Contract, Wanprestasi